Hubungan Tingkat Pengetahuan dan Faktor Lainnya dengan Tingkat Kepatuhan Pasien Hipertensi di RSAL Dr. Mintohardjo Jakarta - Arrang, Sherly Tandi; Veronica, Natalia; Notario, Dion (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
Hypertension is a "silent killer". It is still one of the bigest challenges in Indonesia, where many cases are still found in primary health facilities. Hypertensive patients who require long-term therapy and adherence are very important factors to support the success of therapy. Based on the data from the Ministry of Health of the Republic of Indonesia (2018), 32.3% of hypertensive patients did not take medication regularly. Many factors influence medication adherence, such as level of knowledge, age, gender, working status, and length of illness. This study aimed to determine the effect of the level of knowledge and other factors on the level of medication adherence of hypertensive patients at the Dr. Mintohardjo Naval Hospital (RSAL). This research is a observasional study with a cross-sectional method and uses a questionnaire for data collection. Adherence level questionnaire uses MMAS-8. Analysis of the relationship between factors that influence the level of adherence uses logistic regression. The inclusion criteria of this study included hypertention outpatient aged ≤ 65 years old and are currently receiving antihypertensive therapy. The results of this study showed that out of 284 respondents, 92% of respondents had good knowledge regarding hypertension, while the level of adherence to taking medication was low at 47%. Factors that influence the level of patient adherence to taking medication in this study are gender (p-value = <0.001), education (p-value = <0.001), duration of hypertension (p-value = 0.033), and working status (p-value = <0.001). In contrast, the level of knowledge (p-value = 0.979) and age (p = 0.87) did not significantly influence the level of medication adherence. The Odds Ratio (OR) for working status was 5.73, OR for final education was 2.97, OR for the duration of hypertension was 2.24, and OR for gender was 0.34.